2007
DOI: 10.1097/01.mpa.0000250128.57026.b2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Markers for the Detection of Pancreatic Cancer Through Comparative Serum Protein Expression Profiling

Abstract: PCa is associated with a specific decrease of distinct serum proteins, which allows a reliable differentiation between pancreatic cancer and healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 52 publications
7
100
0
Order By: Relevance
“…In support of this, using serum protein profiling, several groups have recently reported increased serum levels of other apolipoproteins in patients with several types of cancer (Yu et al, 2005;Goncalves et al, 2006). On the other hand, Ehmann et al (2007) recently found that serum levels of different apolipoproteins (ApoA-1 and -2) were decreased in pancreatic cancer patients compared with healthy volunteers. These facts may indicate that several apolipoproteins have different roles in pancreatic cancer development.…”
Section: Apoc-1prevents Apoptosis In Pancreatic Cancer S Takano Et Almentioning
confidence: 86%
“…In support of this, using serum protein profiling, several groups have recently reported increased serum levels of other apolipoproteins in patients with several types of cancer (Yu et al, 2005;Goncalves et al, 2006). On the other hand, Ehmann et al (2007) recently found that serum levels of different apolipoproteins (ApoA-1 and -2) were decreased in pancreatic cancer patients compared with healthy volunteers. These facts may indicate that several apolipoproteins have different roles in pancreatic cancer development.…”
Section: Apoc-1prevents Apoptosis In Pancreatic Cancer S Takano Et Almentioning
confidence: 86%
“…Whereas some studies used undefined protein extracts from tumor lysates (11,14,(28)(29)(30), others focused on limited numbers of candidate tumor antigens (24,25). To our knowledge, only two studies have performed a large-scale profiling of autoantibodies related to cancer using the extensive panel of human antigens present on ProtoArrays, one study probing with 12 colorectal cancer sera and 8 control sera (2), and the other probing with 30 ovarian cancer sera and 30 healthy controls (9).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of human apo A-I in transgenic mice have shown inhibition of tumour growth and improved survival rate. Decreased apo A-I levels have been reported in the serum of patients with pancreatic cancer, gastric cancer, and ovarian cancer [36][37][38]. Apo A-I along with apo A-11, transthyretin are found decreased by more than two fold in pancreatic cancers [36].…”
Section: Anti Tumor Activity Of Apo A-imentioning
confidence: 97%
“…Decreased apo A-I levels have been reported in the serum of patients with pancreatic cancer, gastric cancer, and ovarian cancer [36][37][38]. Apo A-I along with apo A-11, transthyretin are found decreased by more than two fold in pancreatic cancers [36]. Chong et al in their study of gastric cancers got varied expression of apo A-I in plasma in different size tumors.…”
Section: Anti Tumor Activity Of Apo A-imentioning
confidence: 97%